Effects of creatine supplementation on swim power - Ricketts, J. C.; Zachweija, J. J. (Medicine & Science in Sports & Exercise, 1999)
Collegiate swimmers (N = 13) were assigned to a creatine supplementation (N = 7) or placebo group (N = 6). Creatine was given in a CHO drink three times a day for a total of 20 grams per day. Before and after the supplementation period, swim power was assessed using an in-water power rack device. Intermittent sprint swimming consisted of performing on the power rack in the following manner: 20 maximum no-breathing efforts on a 3:1 rest to work ratio. Each trial's performance was the time it took for the weights to reach the top of the rack. Both groups were similar at baseline. One week into the study both groups had improved similarly. However, the creatine group improved significantly more in the last three trials than did the placebo group. Creatine supplementation appears to increase swimming power, above placebo, during the latter part of high repetition, short rest-to-work interval sprint swimming. It has the potential to extend the volume of high quality training. Implication: Creatine supplementation extends a swimmer's ability to continue repeating high quality efforts.